Clinical and laboratory profile of COVID-19 in children below 15 years - Chellappan, Indumathi; Palanisamy, Venkateshwaran; Elangovan, Bharathi (International Journal of Contemporary Pediatrics, 2021)
Background: Coronavirus disease 2019 (COVID-19), in children has varied clinical presentations from asymptomatic infection to severe pneumonia, multi system inflammatory syndrome in children (MIS-C) and rarely death. To date, limited data has been published on the profile of COVID-19 infection among Indian children. The objective of this study was to analyze the clinical spectrum, laboratory parameters, treatment and it’s outcome in children less than 15 years admitted with COVID-19 infection. Methods: This was a cross sectional study done in a tertiary care hospital. Children with COVID-19 infection detected by Reverse transcriptase polymerase chain reaction (RT-PCR) were included. Results: Out of 167 children, 93 were males (55.6%) and median (Interquartile range- IQR) age of children admitted were 9 (4-13) years. Family cluster (71%) was the dominant source of infection. Majority were asymptomatic (60%, N=100). The predominant symptoms were fever (29%), cough (16%) and rhinorrhea (4.1%). Seven (4.1%) children had comorbidities and two (28%) among them had moderate to severe disease. Median (IQR) total leucocyte count was 7 (4-10) ×103 µl and platelet count was 390 (275-500) ×103 µl. Leukopenia was observed in 58% (N=81), lymphocytosis in 32.8% (N=46) and thrombocytopenia in 3.5% (N=5). Inflammatory markers were raised in 10-15% of children. Peri-bronchial cuffing was the common abnormality (N=14, 17.5%) in chest X-ray (CXR) and peripheral heterogeneous opacities were noted in severe disease. Children with moderate to severe symptoms were treated with remdesivir and steroids. Conclusions: COVID-19 infection in children was often benign and increased severity was noted among those with comorbidities. Leukopenia, lymphocytosis were commonly observed. High inflammatory markers were noted in severe disease. Nil fatality among our study group.